Mistreatment of migrant construction workers : Trajectory from the past to the present and into the future - Abdul Rashid, Abdul Aziz; AbdulLateef, Olanrewaju; Poline, Bala (Routledge, 2024)
Labour migration is as old as human history. Based on current and centuries old practices, labour abuse in the construction industry is perhaps as old as humankind. With demographic changes in developed nations and poverty which afflicts labour -rich countries, labour migration is expected to continue in the future. This chapter posits that mistreatment of construction migrants in the future is likely to persist. Urban growth and physical infrastructure development of many nations owe in large part to the internal as well as international movement of construction workers, between developing and developed countries which is often the subject of interest, but also between developing countries and between developed countries. Such traverses give rise to labour abuse being global in nature. So dependent are labour-abundant developing countries on remittances by their citizens abroad that during the drafting of the General Agreement of Trade in Services (GATS), 1 they advocated for free movement of workers to be allowed as part of its provision, but their effort failed. In their final destinations, these migrants are often treated poorly by their construction employers: exploitative wages, insecure employment and forced labour, low safety standards and poor living conditions being the common features. Structural changes in the modern-day construction industry reinforced by discriminatory legislation and judicial systems of host countries have further entrenched undesirable mistreatment of migrants. Central to this poor treatment is the perception of these workers as no more than disposable construction resources. Given these hurdles, this chapter ends by asking whether fair, safe and decent employment will ever be available worldwide for migrant construction workers. All relevant international organisations and nongovernment organisations (NGOs) should orchestrate their efforts for greater impact, as demonstrated by the Global Compact for Safe, Orderly and Regular Migration (usually given the short-hand title 'Global Compact') which was endorsed by the United Nations General Assembly on 19 December 2018.